2020
DOI: 10.3390/foods9060824
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Breast Myopathies through Color and Texture Analyses in Broiler

Abstract: Wooden breast (WB), white striping (WS) and spaghetti meat (SM) are breast myopathies of the Pectoralis major that greatly affect meat quality in broilers. To differentiate color and texture characteristics with instrumental methods, some of them applied for the first time in this species, 300 carcasses were randomly chosen from an abattoir from five different flocks from the same farm, at a rate of 60 carcasses from each flock. Twenty-four hours after slaughter, both side breasts were dissected, and yields ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
10
13
0
Order By: Relevance
“…As concern mineral profile, a study carried out by Tasoniero et al (2020) reported greater calcium and sodium levels in SM samples if compared to unaffected ones, speculating a possible connection between cation homeostasis disturbances and the appearance of pathological mechanisms leading to cell injury development. Intriguingly, the analysis of the available literature highlighted that SM samples possess analogous amounts of total and soluble collagen of unaffected breasts (Baldi et al, 2018;Campo et al, 2020;Tasoniero et al, 2020). On the other hand, Baldi et al (2019) found lower hydroxylysylpyridinoline contents in muscles affected by SM, suggesting a feeble collagen cross-linking (i.e., presence of immature collagen) and corroborating what found from previous histological observations (see section "Histological traits").…”
Section: Implications On Meat Compositionsupporting
confidence: 84%
See 1 more Smart Citation
“…As concern mineral profile, a study carried out by Tasoniero et al (2020) reported greater calcium and sodium levels in SM samples if compared to unaffected ones, speculating a possible connection between cation homeostasis disturbances and the appearance of pathological mechanisms leading to cell injury development. Intriguingly, the analysis of the available literature highlighted that SM samples possess analogous amounts of total and soluble collagen of unaffected breasts (Baldi et al, 2018;Campo et al, 2020;Tasoniero et al, 2020). On the other hand, Baldi et al (2019) found lower hydroxylysylpyridinoline contents in muscles affected by SM, suggesting a feeble collagen cross-linking (i.e., presence of immature collagen) and corroborating what found from previous histological observations (see section "Histological traits").…”
Section: Implications On Meat Compositionsupporting
confidence: 84%
“…However, the growing consumers' demand for thin-sliced chicken breast meat has made the occurrence of SM particularly challenging for the processing industry since, being SM often detectable only after the slicing process, the amount of downgraded/discarded meat could be even exacerbated. Thus, being the in-line detection of abnormal meat a relevant matter especially for the meat packing plants, Morey et al (2020) recently proposed the feasibility of bioelectrical impedance analysis to identify SM breasts, while Campo et al (2020) suggested the analysis of color reflectance as a possible tool to detect those breasts affected by any degree of WS and SM in the processing line. Aside from this, it is noteworthy to mention that SM myopathy cannot be noticed in the living animal, contrarily to WB condition whose presence can be detected by palpating the breast of the live bird and lifting up its wings to assess the ability to achieve back-to-back wing contact (Hosotani et al, 2020).…”
Section: Implications On Meat Quality and Practical Solutionsmentioning
confidence: 99%
“…Thus, there is still need for an objective and fast method to quantify the meat defects. Previous research found that the compression test can be an objective and effective tool to identify and determine the severity of WB ( Mudalal et al, 2015 ; Soglia et al, 2017 ; Sun et al, 2018 ; Campo et al, 2020 ). In this study, despite no severe WB and WS, compression force increased significantly with the increase in WB and WS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Both WS and WB have been reported to affect the water-holding capacity of meat, resulting in higher drip loss and cooking loss, and lower marinade absorption [ 7 , 8 , 9 ]. Moreover, the severity of WB and WS corresponded to higher pH and also higher lightness, redness and yellowness [ 10 ]. In addition, Del Campo et al [ 10 ] reported that the hardness of raw meat increased with the severity of WB.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the severity of WB and WS corresponded to higher pH and also higher lightness, redness and yellowness [ 10 ]. In addition, Del Campo et al [ 10 ] reported that the hardness of raw meat increased with the severity of WB.…”
Section: Introductionmentioning
confidence: 99%